PW 1820 Development of recommendations for falls and fall-related injury prevention among older adults in british columbia, canada. (November 2018) - Samarakkody, Diana; Oakey, Megan; Golmohammadi, Kamran; Angus, Robert; Foucher, Denise; Hussein, Zahra; Kwon, Ashley; Wilson, Kelly
Abstract : Background: In British Columbia (BC), Canada, fall-related injuries are the leading cause of injury-related deaths among seniors (>65 years). On an average day, 40 seniors are hospitalized from fall-related injuries costing $1.3 million in direct healthcare. The majority of these falls occur in the community setting. Objective: Develop evidence-informed recommendations for prevention of fall-related injuries among seniors living in BC communities. Methods: An environmental scan was conducted to identify BC programs and initiatives for prevention of falls among seniors. Opportunities, gaps and barriers were identified to assist with direction and planning of falls prevention programming. Falls Prevention Recommendation Working Group, comprising members representing each Health Authority in BC, with extensive experience in the areas of public health, epidemiology, emergency medicine and falls prevention, was formed. The panel conducted a narrative review of literature, including meta-analyses, systematic reviews, randomized controlled trials, cohort studies, program evaluation and grey literature related to falls and injury prevention among community living older adults. Recommendations were developed through a modified Delphi process and focus groups to develop consensus. Findings: After review of the environmental scan, provincial polices, practice guidelines, training, education, and capacity across BC, as well as a preliminary feasibility assessment, we developed evidence-informed recommendations that included, promoting community awareness together with a comprehensive approach for multifactorial assessments and interventions for those seniors that are at high risk for falls. Conclusion: A multi-disciplinary and multi-agency approach is needed to address complex public health problems such as falls among seniors. Policy implications: For addressing a complex regional public health issue, a similar approach can be used that involves a coordinated and collaborative approach. Steps in such an approach include environmental scan, gap analysis, evidence review, and consensus generation.